Socio-Legal Research: Integration of Normative and Empirical Juridical Research in Legal Research - Afif Noor (PDIH Untag Semarang, 2023)
Legal research is a method used by legal experts to develop legal knowledge. Legal experts have different opinions in explaining the definition of legal science due to differences in opinion in placing legal science as part of social science related to how to apply the law in the practice of legal science is a sui generis science as a practical discipline that establishes standard procedures and guidelines for implementing legal regulations or applied research that has a prescriptive character. The difference in placing the science of science has given birth to the study or field of legal research into normative juridical research and empirical juridical research. Each of these fields has advantages and disadvantages. Therefore, to obtain a comprehensive legal review result, methodological integration is required through an approach called socio-legal research. Socio-legal research is not the same as empirical juridical research, both in the sociology of law and sociological jurisprudence. Socio-legal research is a combination of legal research and social studies of law. Socio-legal research has its objectives and scope, which do not merely look at the law in its empirical questions but also carry out critical academic analysis of the law.